The relevance of culture and religion to the understanding of children's rights in South Africa - Moyo, Precillar (Department of Public Law, 2014)
The aim of this paper is to explore the influence of culture and religion on the rights of the child from a South African perspective. This paper does not engage in a debate about whether children's rights are universal or not. The underlying premise is that children's rights are universal. The paper simply uses the universalism and cultural relativism debate as an entry point to a discussion of children's rights in the South Africa. It will explore the extent to which culture and religion influence and impact the interpretation of children's constitutional rights which are modelled on the CRC. The paper will therefore critically and comparatively consider how South African courts have attempted to reconcile universal norms with historical, cultural and religious peculiarities in defining rights and their resultant effect on children and their welfare.